Variasi Kolesterol Plasma Individual Monyet Ekor Panjang (Macaca fascicularis) sebagai Respons terhadap Diet Aterogenik IPB-1 [INDIVIDUAL PLASMA CHOLESTEROL VARIATION OF CYNOMOLGUS MACAQUE (MACACA FASCICULARIS) IN RESPONSE TO IPB-1 ATHEROGENIC DIET] - Taher, Achmad; Solihin, Dedy Duryadi; Sulistiyani, Sulistiyani; Sajuthi, Dondin; Astuti, Dewi Apri (Jurnal Veteriner, 2017)
The effectiveness of atherogenic diet in raising plasma cholesterol level of cynomolgus macaques(Macaca fascicularis) can be predicted for population, but not for individuals.This study aimed to evaluatethe individual plasma cholesterol of cynomolgus macaques in response to IPB-1 atherogenic diet. Theanimals under study were 22 adult malemonkeys from the animal facility of Primate Research CenterBogor Agricultural University (PSSP IPB). All animals were intervened with the IPB-1 atherogenic diet forthree months and individual plasma cholesterol wasevaluated in a monthly basis.The results showedthat the monkeys’ plasma cholesterol had increased significantly (P <0.05) after one month of interventionperiod and the increases were very significantly different (P <0.01) after three months. Individually, increasesin plasma cholesterol varied among animals. Based on these variations, 2 animals were categorised ashypo-response, 18 animals as hyper-response and 2 animals as extreme.This study showed the variationof individual plasma cholesterol of cynomolgus macaques in response tothe IPB-1 atherogenic diet so thatthe animals might be selected based on the their responsiveness.
Keywords: IPB-1 atherogenic diet; Macaca fascicularis; responsiveness